Ikhtiyār dalam Pemikiran Ekonomi Islam; Perspektif Teologi - Sakinah Fithriyah (Tasfiyah: Jurnal Pemikiran Islam, 2020)
Ikhtiyār is not a strange term in Indonesian language. This word has been absorbed from Arabic language and being an important concept which has a place in Indonesian society worldview. Ikhtiyār as a key terminology in Islamic tradition has a close relationship with the discipline of economics. Both are speaking about ‘choice’ and human behavior. Comprehending the meaning of ikhtiyār as Syed Muhammad Naquib al-Attas has conveyed generates influences in viewing some concepts and ideas in the modern economy which certainly implicate Islamic economics thought. Furthermore, this study is conforming that the differences between Islamic economy and Western one could not only lie at the macroeconomy level, but also relating to the ideas and activities in microeconomy as well. In fact, both are inseparable at all.